2020
DOI: 10.1186/s12933-020-01114-4
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes is an independent predictor of lowered peak aerobic capacity in heart failure patients with non-reduced or reduced left ventricular ejection fraction

Abstract: Background Although type 2 diabetes mellitus (T2DM) is one of the most frequent comorbidities in patients with chronic heart failure (CHF), the effects of T2DM on the exercise capacity of CHF patients are fully unknown. Here, we tested the hypothesis that the coexistence of T2DM lowers CHF patients’ peak aerobic capacity. Methods We retrospectively analyzed the cases of 275 Japanese CHF patients with non-reduced ejection fraction (le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Exercise intolerance is the main symptom in patients with HF, regardless of LVEF ( 32 , 33 ). In these patients, different echocardiographic indices have been shown as important predictors of exercise capacity, particularly raised LV filling pressures ( 34 42 ). Such a relationship can be explained on the basis of reduced stroke volume and pulmonary venous hypertension ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise intolerance is the main symptom in patients with HF, regardless of LVEF ( 32 , 33 ). In these patients, different echocardiographic indices have been shown as important predictors of exercise capacity, particularly raised LV filling pressures ( 34 42 ). Such a relationship can be explained on the basis of reduced stroke volume and pulmonary venous hypertension ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, those studies were either conducted among patients with HFrEF alone, or did not make a distinction between patients according to ejection fraction, while the interplay between diabetes and outcome seems to differ in those populations. In the CHARM trial, the relative risk conferred by diabetes was significantly greater in patients with preserved ejection fraction (EF) than in those with low EF [ 8 ] and a recent study highlighted that the presence of T2D was associated with a reduction of exercise capacity (lower peak VO2) in the LVEF < 40% and LVEF 40–49%, but not in the LVEF > 50% subgroup [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent study, a multivariate analysis showed that the history of DM was an independent predictor of lower VO 2 peak in HF patients, but the impact on exercise capacity was dependent on the systolic dysfunction [ 30 ]. This is in line with the results of our study, where VO 2 peak was lower in DM patients with HFrEF.…”
Section: Discussionmentioning
confidence: 99%
“…But, in the most advanced stages of HF a clear VAT is often not identifiable, which is indices for poor prognosis [ 33 ]. Not only lower VO 2 peak but also reduced VAT was noticed in the diabetic patients with both HFrEF and HF with preserved ejection fraction [ 30 ]. In our work, only in HCTR-nonDM, VAT was reached more often.…”
Section: Discussionmentioning
confidence: 99%